2009
DOI: 10.1002/ejoc.200800922
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Lewis Acid Catalysis in Water: α‐Amino Acids as Effective Ligands in Aqueous Biphasic Catalytic Michael Additions

Abstract: This article explores the potential of native α-amino acids as chiral ligands in aqueous asymmetric Lewis acid catalysis, employing the C-C bond forming Michael addition as a model reaction. Some insights are provided regarding the details of Yb(OTf) 3 /α-amino acid-catalyzed Michael additions in water through new kinetic data as well as studies on how both yield and selectivity are influenced by variations in metal/ligand ratio, pH, temperature, and structure of the α-amino acid. Through this investigation it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…The asymmetric Michael addition using a catalyst made of Yb(OTf) 3 as Lewis acid and L-proline as a chiral ligand (Scheme 94 ) afforded the corresponding addition products with yields up to 94% and high enantioselectivities under environmentally friendly conditions [ 190 ]. The reaction was performed in water as a solvent and the aqueous phase, containing the catalyst, was recycled several times without appreciable loss of catalytic activity.…”
Section: Synthetic Applications In Homogeneous Systemsmentioning
confidence: 99%
“…The asymmetric Michael addition using a catalyst made of Yb(OTf) 3 as Lewis acid and L-proline as a chiral ligand (Scheme 94 ) afforded the corresponding addition products with yields up to 94% and high enantioselectivities under environmentally friendly conditions [ 190 ]. The reaction was performed in water as a solvent and the aqueous phase, containing the catalyst, was recycled several times without appreciable loss of catalytic activity.…”
Section: Synthetic Applications In Homogeneous Systemsmentioning
confidence: 99%
“…With the development of the reaction in water, it is found that the hydrogen bond of the reaction transition state, the hydrophobic effect of the molecular structure, and the solubility of the reactants in water have different influences on the reactions. In particular, in many reactions the use of water as solvent can enhance the reaction activity and selectivity and improve the workup process and catalyst recycling . With in depth research of the reaction in aqueous media, more attention is focused in the enantioselective synthesis under the catalysis of Lewis acids in water.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, quite a few carbon nucleophiles were used as Michael donors to construct the chiral molecules in aqueous media, and most of these asymmetric reactions involved the use of organocatalysts . However, the Lewis acid-catalyzed asymmetric Michael addition in water is rare, and these reactions afford the chiral molecules with poor to moderate enantioselectivities, perhaps due to the effect of water on the coordination of the metal with the chiral ligand. As for the asymmetric metal-catalyzed Michael addition reaction in aqueous media, we only found one publication for the addition of thiols to α, β-unsaturated ketones in water to afford the β-keto sulfides .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies of Lindstrom 44 show that the water tightly coordinated to the metal halide become more labile upon complexation of an organic ligand (electrophile), leading to a higher rate of exchange with substrate molecules and consequently to higher reaction rates.…”
Section: Introductionmentioning
confidence: 99%